Clinical, Laboratory and Risk Factors for COVID-19 Mortality in the Elderly Population of Iran: A Three-year Cross-sectional Study - Mousavi, Mohammad Javad; Arefinia, Nasir; Motaarefi, Hossein; Azarsa, Mohammad; Behboudi, Emad (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To investigate the clinical characteristics, laboratory findings, and risk factors associated with COVID-19 mortality among elderly patients in Khoy, West Azerbaijan, Iran. METHODOLOGY: This retrospective cross-sectional study analyzed data from 447 confirmed COVID-19 patients over 60 years old hospitalized in Khoy's referral hospital between March 2020 and December 2022. The diagnosis was confirmed via RT-qPCR based on Iran's national protocol. Demographic, clinical, and laboratory data were extracted from hospital records and the city health centre using a standardized checklist. RESULTS: Significant risk factors for mortality included patient gender, hospital admission route, and the presence of severe clinical symptoms such as dyspnea, hypoxia, myalgia, altered consciousness, and high fever. Among comorbidities and lifestyle factors, diabetes, neurological disorders, smoking, and lung diseases were significantly associated with increased mortality risk. Except for platelet count and alanine aminotransferase (ALT) levels, all other laboratory parameters demonstrated significant differences between recovered and deceased patients. CONCLUSION: This study highlights the importance of considering age, gender, clinical presentation, and pre-existing conditions when managing elderly COVID-19 patients to mitigate complications and reduce mortality. Targeted interventions and enhanced monitoring strategies for high-risk individuals are essential to improve outcomes in this vulnerable population.